Black social work students' experiences of practice learning: Understanding differential progression rates. (November 2014) - Fairtlough, Anna; Bernard, Claudia; Fletcher, Joan; Ahmet, Akile
Summary: As a group, Black and ethnic minority students progress more slowly on their social work programmes in England than their white counterparts. The article reports on a qualitative study with social work students and key informants in a purposive sample of eight social work programmes. Findings: Factors relating to the characteristics of individual students, the social work programme, the HEI and practice learning environments appeared to be affecting student experience and progression. The article focuses on practice learning. Many student participants reported experiences of disadvantaged educational backgrounds, economic pressures and caring responsibilities. Key informants in some sites described particular challenges faced by these students. Students reported experiences of racism in placements where the majority of staff or service users were white. Application: Concepts drawn from work by Pierre Bourdieu such as 'habitus', 'field' and 'social and cultural capital' are used to make sense of these findings. Some practical ways in which social work programmes might seek to counter educational disparities and racism faced by black and ethnic minority students are suggested: these include monitoring systems, training for practice educators and tutors, support for black and ethnic minority students and agreements between HEIs and placement providers.